Asymmetric key algorithms-A Proposed Method (International Journal of Engineering and Computer Science, 2017)
Asymmetric key algorithms use different keys for encryption and decryption. The encryption key is public, decryption key is secret. Anyone can encrypt a message but only the one who knows the corresponding private key can decrypt it. This paper discuss asymmetric key algorithms with its advantages and disadvantages.